The insertion of anti-corruption education into Islamic education learning based on neuroscience - Suyadi Suyadi; Zalik Nuryana; Anom Wahyu Asmorojati (Institute of Advanced Engineering and Science, 2021)
This research aimed to analyze the insertion of anti-corruption education in Islamic education. In the context of anti-corruption education, especially students in tertiary institutions, corrupt practices are manifested in the form of corrupt behavior, such as plagiarism, cheating, truancy, and hitchhiking in group assignments, even though they do not contribute. Anti-corruption education in Islamic education has so far used a dogmatic approach, not using an approach that has a transformative impact, especially neuroscience. In this case, Universitas Ahmad Dahlan, with lecturers who have special competence as anti-corruption trainers, has carried out anti-corruption education in various scientific fields, including Islamic education. This phenomenological type of qualitative research involved 52 students and six lecturers in the master study program of Islamic education. The results showed that anti-corruption education was carried out through insertion into all relevant subjects, especially the neuroscience of Islamic education. The lecturer investigates students' corrupt behavior in anticipation of future corruption crimes. The investigation results show that the most corrupt behavior of students is plagiarism, taking names in group assignments, and leaving absences with friends. The insertion of anti-corruption education with a neuroscience approach is applied in building integrity awareness that corrupt behavior is contrary to how the brain works and even has the potential to destroy reason.